Potent effects of roniciclib alone and with sorafenib against well-differentiated thyroid cancer. Issue 10 (October 2018) - Lin, Shu-Fu; Lin, Jen-Der; Hsueh, Chuen; Chou, Ting-Chao; Wong, Richard J
Abstract : Activation of cyclin-dependent kinase activity is frequently observed in many human cancers; therefore, cyclin-dependent kinases that promote cell cycle transition and cell proliferation may be potential targets in the treatment of malignancy. The therapeutic effects of roniciclib, a cyclin-dependent kinase inhibitor for papillary and follicular thyroid cancer (designated as well-differentiated thyroid cancer), were investigated in this study. Roniciclib inhibited cell proliferation in two papillary and two follicular thyroid cancer cell lines in a dose-dependent manner. Roniciclib activated caspase-3 activity and induced apoptosis. Cell cycle progression was arrested in the G2/M phase. Roniciclib treatment in vivo retarded the growth of two well-differentiated thyroid tumors in xenograft models in a dose-dependent fashion. Furthermore, the combination of roniciclib with sorafenib was more effective than either single treatment in a follicular thyroid cancer xenograft model. Acceptable safety profiles appeared in animals treated with either roniciclib alone or roniciclib and sorafenib combination therapy. These findings support roniciclib as a potential drug for the treatment of patients with well-differentiated thyroid cancer.